Madhuca balakrishnanii (Sapotaceae), a new species from Kerala, India - Kumar, Ettickal Sukumaran Santhosh; Shailajakumari, Sreedharan; Shareef, Sainudeen Muhammed (Phytotaxa, 2021)
Madhuca balakrishnanii (Sapotaceae), a new species from Kerala is here described with photographs. It is most closely similar to M. diplostemon and M. insignis but differs in having long stipules, sparsely hairy pedicels, abaxially hairy inner sepals, shorter corolla tubes with oblong lobes, fairly long densely hairy staminal filaments, shorter styles and ovoid fruits. The IUCN conservation status, ecology, distribution and phenology along with a key for the identification of Madhuca species in the Western Ghats is provided.